Africa wired - United Nations (Africa Renewal, 2012)
It’s elegant, it’s hip and it’s one of the hottest phones on the African market. Nothing says “I am important” like a man or woman whipping out a BlackBerry smartphone. It’s easily recognizable with its wide screen and trademark keypad. According to Masahudu Ankiilu Kunateh, editor at Ghananewslink.com, “What is your BB pin?” has become the ultimate sizingup request. To be asked the question, he says, you have to be considered cool enough to own one.